Diatom‐inferred microtopography formation in peatlands. Issue 2 (17th November 2021) - Chen, Xu; McGowan, Suzanne; Bu, Zhao‐Jun; Huang, Xian‐Yu; Bai, Xue; Zhang, Yu‐Ke; Peng, Jia; Li, Jun‐Lu
Abstract: Peatlands, an important carbon pool in terrestrial ecosystems, are often characterised by a hummock–hollow microtopography, which has important implications for hydrologic conditions, biotic community structure and carbon cycling. However, dynamics of microtopography formation are poorly understood. Moss‐inhabiting diatoms are sensitive to water table change and may be used to infer microtopography formation. Sixty‐three surface moss samples were collected from four Sphagnum peatlands in the Changbai Mountains (north‐eastern China), covering a water table gradient of 0–55 cm. Ordination analyses revealed that depth to the water table (DWT) was the determinant of diatom distribution, and its sole effect explained 15% of total variance in diatom composition. Accordingly, a diatom‐based water table transfer function was developed using a weighted averaging model with inverse deshrinking ( R 2 = 0.82, RMSEP = 5.63 cm with leave‐one‐out cross validation), and applied to diatom records of a Sphagnum hummock profile. Quantitative reconstruction of DWT showed that the height of the Sphagnum hummock increased obviously in the early stage and then remained relatively stable when the reconstructed height was more than 35 cm. The results suggested that annual addition of Sphagnum litter exceeded its decomposition during the early stage of hummock formation, and Sphagnum production and decomposition reached equilibrium when the hummock had grown to a certain height. This is the first study to explore dynamics of hummock height using moss‐inhabiting diatoms, and hence provides a novel tool for quantitative reconstruction of microtopography formation in Sphagnum peatlands. Abstract : A novel diatom‐based water table transfer function was established in peatlands.The transfer function was used to reconstruct microtopography dynamics.Diatoms can improve our understanding of biogeomorphic processes in peatlands.